2022
DOI: 10.5935/1984-0063.20220025
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ sleep quality during the COVID-19 pandemic

Abstract: Objective: To assess the sleep quality of Brazilian adolescents during the COVID-19 pandemic. Methods: Observational, analytical, cross-sectional study with data from a questionnaire on individual characteristics and health, Epworth Sleepiness Scale and the Pittsburgh Sleep Quality Index (PSQI). 153 adolescents participated -61.4% females, 38.6% males, aged 13 to 18 years, enrolled at school. Results: 58.2% worsened their sleep quality during the pandemic. In the PSQI, 22 (14.4%) had a good, 104 (68%), a poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
(24 reference statements)
3
13
0
Order By: Relevance
“…This study found that younger children (0–3 years old) experienced longer sleep latency, delayed bedtime, and reduced sleep duration during confinement compared with older children (3–6 years old) during COVID‐19 isolation (Markovic et al, 2021 ). The second study showed that 58.6% of the children aged (0–3 years) experienced worse sleep quality, and 39.4% of the children experienced nocturnal awakenings in agreement with the first study (Silva et al, 2022 ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This study found that younger children (0–3 years old) experienced longer sleep latency, delayed bedtime, and reduced sleep duration during confinement compared with older children (3–6 years old) during COVID‐19 isolation (Markovic et al, 2021 ). The second study showed that 58.6% of the children aged (0–3 years) experienced worse sleep quality, and 39.4% of the children experienced nocturnal awakenings in agreement with the first study (Silva et al, 2022 ).…”
Section: Resultssupporting
confidence: 87%
“…The Pittsburgh Sleep Quality Index (PSQI) scale was used in five studies and was the most commonly used scale in adolescents. Three studies found that sleep quality worsened during the COVID‐19 pandemic (Silva et al, 2022 ; Windiani et al, 2021 ; Zhou et al, 2020 ). Two studies pointed to an increased prevalence of sleep disturbances (Windiani et al, 2021 ; Zhou et al, 2020 ), and four studies showed an increase in sleep duration during COVID‐19 in adolescents (Genta et al, 2021 ; Silva et al, 2022 ; Windiani et al, 2021 ; Zhou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that during the pandemic adolescents' sleep quality was severely affected by the mobile phone use pattern, stress level, and sleep pattern, and that this can also weaken immune responses to infection (122)(123)(124)(125). Teenagers with weak self-regulation and self-control would be unable to resist their inner need to use mobile phones (e.g., escape motive), which may lead to an uncontrolled rise in mobile phone usage time and, ultimately, to problematic mobile phone use (PMPU).…”
Section: Discussionmentioning
confidence: 99%